2014
DOI: 10.1586/14737175.2014.887444
|View full text |Cite
|
Sign up to set email alerts
|

Tissue engineering of the peripheral nervous system

Abstract: The structure and function of peripheral nerves can be affected by a range of conditions with severe consequences in these patients. Currently, there are several surgical techniques available to treat peripheral nerve defects. Direct repair is the preferred treatment for short nerve gaps, and nerve autografting is the gold standard in critical nerve defects. The autografting is not always available, and the use of allograft, decellularized allograft and nerve conduits are often used with variable success. Duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
142
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 200 publications
0
142
0
1
Order By: Relevance
“…33 There are many factors that impact the efficacy of nerve conduits, including thickness, porosity, and flexibility. Studies have shown that the conduit thickness is closely related to neuroma formation, 34 and that thicknesses greater than 0.81 mm attenuate axonal outgrowth. 35 The association between increased conduit wall thickness and decreased nerve regeneration is likely mediated by decreased nutrient diffusion and wall porosity.…”
Section: Methodsmentioning
confidence: 99%
“…33 There are many factors that impact the efficacy of nerve conduits, including thickness, porosity, and flexibility. Studies have shown that the conduit thickness is closely related to neuroma formation, 34 and that thicknesses greater than 0.81 mm attenuate axonal outgrowth. 35 The association between increased conduit wall thickness and decreased nerve regeneration is likely mediated by decreased nutrient diffusion and wall porosity.…”
Section: Methodsmentioning
confidence: 99%
“…These conduits require a second surgery in order to remove the non-resorbable material. The original idea was to provide support, structure to guide axonal regrowth and form a stable barrier against connective tissue infiltration [73,100,101]. Synthetic nerve conduits made of ePTFE were successfully applied in a 4-cm nerve gap, in human [102].…”
Section: Manufactured Conduitsmentioning
confidence: 99%
“…While a variety of synthetic and biopolymers, such as collagen, polycaprolactone, polyglycolic acid, poly-DL-lactide-co-caprolactone (PLCL), and polyvinyl alcohol (PVA), [9] have been explored as scaffold materials, geometry of these devices remains largely limited to simple cylindrical lumens with millimeter dimensions [1013]. Since individual fascicle dimensions are on the order of microns, which is ~1000 times smaller than typical scaffolds, the role of the channel size on Schwann cell migration and axonal growth remains poorly understood especially for channels smaller than 200 μm.…”
Section: Introductionmentioning
confidence: 99%